Hubungan Stres Kerja dengan Dismenorea pada Operator Mesin Jahit - Dini Widianti (Lembaga Penelitian Universitas YARSI, 2018)
The objective of this study is to know the association between stress at work and dysmenorrhea. Dysmenorrhea has a direct big impact on individual and company. Problems that arise are associated with increased absenteism, resulting in reduced productivity. A cross-sectional study has been carried out, using total sample of 165 workers who operate sewing machine at ‘PT X’ Jakarta. The instruments used for this study is Stres Diagnostic Survey questionnaire to measure stress at work and another questionnaire for identifying dysmenorrhea and other risk factors. Analytical techniques used Chi-Square and logistic regression. The prevalence of dysmenorrhea was 37%, and prevalence for stres at work was 25,4%. High level stres at work have arise 2,24 times with dysmenorrhea (p value 0,029 ; OR value 2,27 and 95% CI: 1,08 – 4,76) also with work period over five year (p value 0,010 ; OR Value 0,36 and 95% CI : 0,16 – 0,78) is decrease dysmenorrhea 64% . This study has shown that dysmenorrhea among workers of sewing machine operate at ‘PT X’ Jakarta was correlation with high level stress at work and work period less than five year